2020
DOI: 10.1016/j.jeconom.2020.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Testing identification strength

Abstract: We consider models defined by a set of moment restrictions that may be subject to weak identification. We propose a testing procedure to assess whether instruments are "too weak" for standard (Gaussian) asymptotic theory to be reliable. Since the validity of standard asymptotics for GMM rests upon a Taylor expansion of the first order conditions, we distinguish two cases: (i) models that are either linear or separable in the parameters of interest (ii) general models that are neither linear nor separable. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Using this characterization of varying identification strength, Antoine and Renault (2020) have devised a testing strategy that is capable of detecting (certain levels of) instrument strength in nonlinear models estimated by GMM. The proposed test, dubbed the distorted J-test (DJ test), is based on computing the GMM J-test statistic at a slightly perturbed value of the continuously updated GMM (CUGMM) estimator.…”
Section: Testing For Instrument Strength: Existing Literaturementioning
confidence: 99%
See 4 more Smart Citations
“…Using this characterization of varying identification strength, Antoine and Renault (2020) have devised a testing strategy that is capable of detecting (certain levels of) instrument strength in nonlinear models estimated by GMM. The proposed test, dubbed the distorted J-test (DJ test), is based on computing the GMM J-test statistic at a slightly perturbed value of the continuously updated GMM (CUGMM) estimator.…”
Section: Testing For Instrument Strength: Existing Literaturementioning
confidence: 99%
“…Interestingly, Antoine and Renault (2020) have demonstrated that their DJ test is akin to the standard rule-of-thumb when the model is linear and homoskedastic. In contrast, they stress (see also Windmeijer, 2019 for related work in the context of clustering) that this DJ test differs from standard "robustified" versions of the rule-of-thumb in case of a heteroskedastic linear model.…”
Section: Testing For Instrument Strength: Existing Literaturementioning
confidence: 99%
See 3 more Smart Citations